A bioanthropological perspective on the Punic period in Ibiza (Spain) as evidenced by human skeletal remains - Márquez-Grant, N (2006)
﻿ The Punic period (6th - 2nd century BC) in the island of Ibiza (Spain) has been regarded by historians and archaeologists as a time of flourishing economic wealth and prosperity, as evidenced by its coin production, demographic growth, agricultural exploitation, intensive product manufacturing and its overall importance to Punic trading routes. From a bioanthropological perspective, this apparent prosperity raises a number of interesting questions. Did such prosperity manifest itself in the biological well-being of the population? What were the morbidity rates like for the inhabitants of Ibiza? Were there differences between urban and rural populations? How might this period compare with a less prosperous era? These questions led to the following hypothesis being established - General prosperity in the Punic period in Ibiza should be reflected in the general wellbeing of the population, as evidenced by human skeletal remains. To test this hypothesis, morbidity rates in the general population in the Punic period were assessed including an analysis of rural and urban populations. In addition the Punic period was compared to the Late Antiquity - Early Byzantine (4th - 7th century AD) period. To assess these issues, anthropological data on stature, oral health, infections, trauma, mortality, osteoarthritis and diet was analysed, amongst other indicators. Allied to this, the research attempted to place the analysis in a broader biocultural context. Whether the above questions could be definitively answered depended on the sample size of material available. A larger sample would certainly have allowed these issues to be explored in even more depth than was possible in this study. Nevertheless, the samples studied have produced a range of interesting results that will aid future research. This research provides a wider understanding of the Punic period in Ibiza and of the Punic world in the Western Mediterranean; highlights the importance of combining anthropological work with other archaeological data; contributes to the osteological and palaeopathological record for Ibiza; and finally, provides a framework for further research.